Lipid peroxidation and histological changes in rat thymus tissue after administration of cisplatin and dexamethasone - Yavroyan, Z. V.; Hakobyan, N. R.; Grigoryan, A. V.; Hovhannisyan, A. G.; Abgaryan, T. A.; Gevorgyan, E. S.; Karapetyan, A. F.; Asatryan, A. L. (Regulatory Mechanisms in Biosystems, 2026)
The thymus gland plays a crucial role in immune function in both healthy and tumor-bearing organisms and it is particularly sensitive to antitumor drugs, such as cisplatin. It is well known that cisplatin causes significant toxicity, to reduce which, dexam e thasone is commonly included in combination chemotherapy regimens. It should be noted that the mechanisms of their combined effects are incompletely studied. The aim of this study was to identify the correlation between the level of lipid peroxidation and histological changes in rat thymus tissue after separate and combined administration of cisplatin and dexamethasone. The experiment was conducted on four groups of animals: a control group, an experimental group with cisplatin injection, an experimental group that received dexamethason and an experimental group that received combined injection of these drugs. In homogenates and supernatants of thymus tissue of rats from all experimental groups quantitative assessment of conjugated dienes was performed by spectrophotometric method after extraction with a mixture of heptane-isopropyl alcohol. The oxidative stress marker malondialdehyde (MDA) was quantified by thiobarbituric acid analysis. Catalase activity was measured by the ammon i um molybdate method. Superoxide dismutase (SOD) activity was assessed by the change in the amount of adrenaline autooxidation product. Thymus tissue samples were fixed and processed using standard histological protocols for histological evaluation. The data show that cisplatin and dexamethasone exerted significant increase in the level of conjugated dienes in homogenate of thymus tissue by 113%, 104% and 143% respectively after their separate and combined use. The amount of MDA also increase d significantly as a result of both the separate and combined effects of cisplatin and dexamethasone in homo g enate and in supernatant of thymus tissue. These quantitative alterations of both conjugated dienes and MDA indicates a prom o tion of oxidative stress. Catalase and SOD, which are part of the cell’s antioxidant system, also exhibit sensitivity to cisplatin and dexamethasone. Follow ing both the separate and combined injection of cisplatin and dexamethasone , a significant reduc tion in the activity of the antioxidant enzymes in homogenates was regist er ed. At the same time, the quantitative changes in conjugated dienes and MDA level as wel l as decrease in catalase activity and SOD recorded in the supernatant we re more modest. In fact, these drugs induced oxidative stress (OS) via reduction of catalase and SOD activities. In addition, the results of histomorphological analysis indicate the thymotoxic effect of cisplatin and dexamethasone. The finding results confirmed that these drugs demonstrate pro-oxidant and thymotoxic effects, although they act through different molecular mechanisms. The d ifferent molecular mechanisms of action of cisplatin and dexamethasone shape the outcome of their combined use. In this case, dexamethasone plays a “preventive” role, likely due to its unique pharmacological properties and mechanisms of action.